Cash Wakaf's Contribution to Islam's Socio-Economic Development in Perak - Shafiai, Mohd Zaini; Musa, Armiadi; Muthalib, Salman Abdul (Media Syari'ah, 2024)
This article aims to discuss the role of cash waqf in the socio-economic development of Muslims in the country of Perak. Cash Waqf is a new product of fiqh today. Because, initially the discussion about waqf referred to non-transferable assets ('iqar) and transferable assets (manqul). Waqf Perak Ar Ridzuan (WPAR) which was launched in 2015 aims to overcome the problem of lack of cash waqf funds. This article explains the implementation of WPAR cash waqf from 2016 to 2021. This research is qualitative in nature through a semi-structured interview protocol with the management of the Perak Islamic Religion Council (MAIPk). The research results found that the implementation of cash waqf focuses on four main areas, namely economics, education, health and religion. In the economic sector, bot waqf funds and waqf business centers (WBC) help increase the income and standard of living of Muslims. Meanwhile, in the education sector, the focus is on endowments for student dormitory buildings and the MUMTAZ program. Meanwhile, in the health sector, hemodialysis center facilities have been built and in the religious sector, funds have been created for the development of maahad tahfiz and the development of Al-Quran knowledge. The findings of this research prove that increasing WPAR fund collection can develop the socio-economic development of Muslims in the country of Perak.  It is hoped that the implications of this research can provide a valuable contribution and serve as a guide for MAIPk, in managing waqf so that it can empower cash waqf in the country of Perak.